Clinical nursing education during the COVID-19 pandemic: perspectives of students and clinical educators - Omolhoda Kaveh; Fahimeh Ghasemi Charati; Mahsa Kamali; Fereshteh Araghian Mojarrad (BMC, 2022)
Abstract Background The outbreak of the COVID-19 pandemic has thus far disrupted clinical nursing education (CNE) around the world and in Iran; which has encountered numerous challenges to this point for students and clinical educators. Therefore, this qualitative study was conducted to identify the perspectives of nursing students and clinical educators during the COVID-19 pandemic. Methods In this qualitative descriptive study, 15 participants, including nursing students and clinical educators, were selected through the purposive sampling method. The data were collected from March to September 2021 in nursing school through in-depth semi-structured interviews, and then analyzed based on the Graneheim and Lundman method. Results Two main themes, "CNE in the shadows of threats and opportunities" and "CNE recovery" and five themes (Injured CNE, CNE under fear, Lessons from the COVID-19 crisis, Providing optimal CNE by eradicating COVID-19, and Adapting CNE to existing conditions) were extracted from the data analysis. Conclusions The results of this qualitative study demonstrated that the COVID-19 pandemic had led the participants to experience new conditions, also referred to as "combined threats and opportunities". Based on this, nursing managers and planners are advised to take great steps towards the development and improvement of CNE by considering and applying these results in their plans to overcome the challenge of CNE with effective and useful actions in the COVID-19 pandemic.